2016
DOI: 10.1097/fpc.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Hla-B*57

Abstract: Retrospective data from 5 years of experience have confirmed the cost-effectiveness of the systematic genotyping in candidate patients for ABC therapy, and have shown that cost-effectiveness is a dynamic parameter closely linked to allele prevalence and pharmacological therapy costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The prevalence of an allele of interest influences the positive predictive value of the genetic test (Ademi et al 2017; Alagoz et al 2016; D’Andrea et al 2016; Gonzalez et al 2015; Grosse 2015; Ke et al 2017; Lee et al 2014; Moretti et al 2017; Naylor et al 2014; Plothner et al 2016; Ruiz-Iruela et al 2016; Snowsill et al 2017). This, therefore, increases the effectiveness of “cascade” screening programs where, for example, an individual is identified by clinical prescreening as having an increased risk of having the allele/mutation (Ademi et al 2014; Lazaro et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of an allele of interest influences the positive predictive value of the genetic test (Ademi et al 2017; Alagoz et al 2016; D’Andrea et al 2016; Gonzalez et al 2015; Grosse 2015; Ke et al 2017; Lee et al 2014; Moretti et al 2017; Naylor et al 2014; Plothner et al 2016; Ruiz-Iruela et al 2016; Snowsill et al 2017). This, therefore, increases the effectiveness of “cascade” screening programs where, for example, an individual is identified by clinical prescreening as having an increased risk of having the allele/mutation (Ademi et al 2014; Lazaro et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The cost of treatment, if the treatment is a “companion” treatment, also influences the cost-effectiveness of PM (Buchanan et al 2017; Horster et al 2017; Jahn et al 2015; Lim et al 2016; Ruiz-Iruela et al 2016). A companion treatment is marketed together with a specific genetic test.…”
Section: Resultsmentioning
confidence: 99%
“…Following randomized control trials, it was shown that expression of HLA-B∗57:01 has a 100% negative predictive value and a 47.9% positive predictive value for the development of abacavir hypersensitivity [22]. Genotype screening for HLA-B∗57:01 was therefore approved clinically by regulatory authorities after findings demonstrated that screening for this allele could effectively eliminate the incidence of hypersensitivity reactions [23,24]. Likewise, the food and drug administration has recommended screening for HLA-B∗15:02 in south east Asian patients where carbamazepine treatment is indicated due to an association with the development of SJS/TEN [12,25,26].…”
Section: The Heterogenous Nature Of Drug Hypersensitivity Reactionsmentioning
confidence: 99%
“…[77,78] One example of a PGx test with wide support is the HLA-B*57 for patients to be prescribed the drug abacavir. [79] While evidence is accumulating regarding clinical benefit for several types of genomic applications, the paucity of studies is a major factor influencing coverage decisions. [80] The cost-effectiveness of PGx testing for some patients has not been demonstrated [81] or in some cases, testing may only be cost-effective in high-risk patient populations.…”
Section: Barriers To Test Utilizationmentioning
confidence: 99%